(3ehGgH GdCagGe aj TQM TQGFY GdESdGes - (3eMeO egOj Hf GdMSf Hf CMeO GdMSjfj GdbRhjfj GdfLaj,J (B1300 (3g` s
(3ChdgG (B:s
(3GdaUd GdKGfi ai GdcdGe hgh jTJed Ydi HjGfg heG jJYdb Hg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B114s
Keywords: (3abg GdePGgH GdCNQis